Genetic polymorphism of β-lactoglobulin and κ-casein of cattle breeds in Croatia - Ante Ivanković; Jelena Ramljak; Admir Dokso; Nikolina Kelava; Miljenko Konjačić; Saša Paprika (Mljekarstvo)
Profitable milk production respects the interests of producers, processing industries, consumer requirements and welfare of animals. Development of new methods of direct gene analysis responsible for milk proteins polymorphism provide new tools to raise the profitability of milk production and dairy products through implementation of breed genetic profile in breeding program. Because of necessity to determinate genetic profiles of cattle breeds in Croatia using new analytical methods, the ratio of dominant allelic polymorphic variants of beta-lactoglobulin (β-Lg) and kappa-casein (κ-CN) is defined. The share of beta-lactoglobulin B variant is dominant in all investigated cattle breeds (>52.9 %). Kappa- casein allelic variant A is dominant in selected cattle breeds (60.7-76.4 %), while the share of B variant is significantly more presented in autochthonous cattle breeds (48.2-84.1 %). Knowledge about genetic profile of breeds due to studied polymorphic variants of milk proteins is useful in further breeding development and economic reaffirmation of cattle breeds, especially autochthonous ones.